1999
DOI: 10.1073/pnas.96.20.11200
|View full text |Cite
|
Sign up to set email alerts
|

Verification of phylogenetic predictions in vivo and the importance of the tetraloop motif in a catalytic RNA

Abstract: M1 RNA, the catalytic subunit of Escherichia coli RNase P, forms a secondary structure that includes five sequence variants of the tetraloop motif. Site-directed mutagenesis of the five tetraloops of M1 RNA, and subsequent steady-state kinetic analysis in vitro, with different substrates in the presence and absence of the protein cofactor, reveal that (i) certain mutants exhibit defects that vary in a substratedependent manner, and that (ii) the protein cofactor can correct the mutant phenotypes in vitro, a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
(22 reference statements)
2
19
1
Order By: Relevance
“…coli RNase P has no ATPase activity. Previous reports (15,16) show that during precursor tRNA cleavage, some unwinding of the substrate occurs. By analogy, a similar unwinding of substrate must occur during cleavage by eukaryotic (human) RNase P. However, we have not yet been able to demonstrate directly any helicase activity associated with either E. coli or human RNase P with the substrate we used.…”
Section: Discussionmentioning
confidence: 99%
“…coli RNase P has no ATPase activity. Previous reports (15,16) show that during precursor tRNA cleavage, some unwinding of the substrate occurs. By analogy, a similar unwinding of substrate must occur during cleavage by eukaryotic (human) RNase P. However, we have not yet been able to demonstrate directly any helicase activity associated with either E. coli or human RNase P with the substrate we used.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of hairpins from ribosomal RNA and other sources have suggested that a tetraloop structure could increase the thermodynamic stability of an RNA duplex, or act as a docking site for intramolecular or intermolecular RNA-RNA interactions (124)(125)(126)(127)(128)(129)(130). In E. coli RNase P RNA (M1 RNA), a mutation in the L9 loop results in a reduction in K m and k cat of the holoenzyme-catalyzed reaction with pre-4.5S RNA as substrate (131), but little effect on pre-tRNA processing in vitro.…”
Section: (18)mentioning
confidence: 99%
“…These tetraloops are important for stabilization of the tertiary structure of the RNA through long distance interactions between L9 and P1 [ 32 ], and between L14 and L18 with P8 [ 33 ] ( Figure 1 and Figure S2 ). These tertiary interactions have been shown to be functionally relevant in E. coli [ 34 ]. Therefore the absence of intramolecular stabilizing tertiary interactions could be a possible explanation for the catalytic deficit of plastid RPRs (below).…”
Section: Resultsmentioning
confidence: 99%